Prevalence of Gastrointestinal Helminthes and Protozoa Among Stray Dogs in Baghdad - Hadi, Afkar M.; Faraj, Azhar A. (The Iraqi Journal of Veterinary Medicine, 2022)
The aim of this study is to identify the gastrointestinal parasites and Protozoa in stray dogs.  The current study includes seven genera of intestinal helminths and protozoa as follows: one cestode (Taenia sp. 29.1%), four nematodes (Hookworm 86.6%, Toxocara canis 67.5%, Trichuris vulpis 51.6% and Strongyloides sp. 5%) and two protozoa (Giardia sp. 24.1% and Cryptosporidium sp. 20.8%) from 120 fecal samples of dogs were collected from different regions of Baghdad during the period from February to July 2014. The results revealed that the intestinal parasites appeared in all months of the study; however, the high infection rate was during the winter months.